Comprehensive model of short‐ and long‐term slow slip events in the Shikoku region of Japan, incorporating a realistic plate configuration. Issue 19 (10th October 2013) - Matsuzawa, Takanori; Shibazaki, Bunichiro; Obara, Kazushige; Hirose, Hitoshi
<x xml:space="preserve">Abstract</x> [1] We numerically simulate slow slip events (SSEs) in the Shikoku region of Japan, incorporating the configuration of the subducting plate. We adopt a rate‐ and state‐dependent friction law with cutoff velocities, assuming a frictional parameter distribution based on observed long‐term SSEs and nonvolcanic tremors that reflects the slip of short‐term SSEs. Our model reproduces recurrences of long‐ and short‐term SSEs and segments of short‐term SSEs. In our simulation, short‐term SSEs' transition from episodic to continuous slip is reproduced. This feature is consistent with tremor activity recently reported in both Shikoku and Cascadia. In addition to the long‐term SSEs in the Bungo Channel, our model also reproduces newly found long‐term SSEs in central Shikoku and predicts that these SSEs recur during the interseismic period between megathrust earthquakes. Our model comprehensively reproduces various SSEs and their characteristics as reported in the Shikoku region.